THE EFFECT OF COLLEGE GAMES ON FINE MOTOR DEVELOPMENT IN PRE-SCHOOL - Fauziah Rudhiati; Nunung Nurjanah; Suci Raihany; Andria Pragholapati (NHM PRESS, 2021)
Background: According to Riskesdas (2018) the preschooler development index only reaches 64.6%. Based on the phenomenon in TK Pembina Cimahi, 5 out of 10 students have not been able to perform fine motor activities according to their age stages, thus the fine motor development need improved by providing appropriate stimulation, which one play a collage game, so that child was develop according to his age. This study aims to determine on play collage game affected of fine motor development in preschooler at TK Pembina Cimahi.The method used a quasy one group pre-test post-test with control group experiment, 16 respondents did a usual activity. Each group was measured with a checklist of fine motor development before and after intervention.The results of this study the intervention group had higher average of fine motor development values, so it was expected that nurses could carry out collage games in accordance with SOP (Standard Operating Procedures) through the Toddler Family Development Program (BKB), which could optimize of fine motor development in preschooler.